AN ANALYSIS OF ENGLISH CODE MIXING USED BY MAIN CHARACTER IN KAGET NIKAH FILM - Yasinta Trililis Anjelina Maduwu; Devi Tri Romadhoni; Syafrianto SM (Universitas Duta Bangsa Surakarta, 2023)
The phenomenon of code mixing is often used in communication. In this case, people sometimes mix language into other languages to gain understanding and communication success. The purpose of this study is to determine the type of insertion in code mixing used in the film